Ekonomska preobrazba slovenskih mest - Bole, David (ZRC SAZU, Založba ZRC, 2022)
The economic transition in Slovenia has undoubtedly led to major changes in Slovene urban landscape. The political transition in the 1990-ies was only the beginning of other fundamental processes that followed: the socialistic economic system started collapsing, new markets emerged and cities were exposed to global socioeconomic forces. Slovene cities were and still are at the forefront of the mentioned change. Major spatial, cultural, social and other transformations as results of the economic transition can be seen and felt by citizens, workers and visitors.